2004
DOI: 10.1155/s0161171204308094
|View full text |Cite
|
Sign up to set email alerts
|

The Poisson equation in homogeneous Sobolev spaces

Abstract: We consider Poisson's equation in an n-dimensional exterior domain G(n≥2) with a sufficiently smooth boundary. We prove that for external forces and boundary values given in certain Lq(G)-spaces there exists a solution in the homogeneous Sobolev space S2,q(G), containing functions being local in Lq(G) and having second-order derivatives in Lq(G) Concerning the uniqueness of this solution we prove that the corresponding nullspace has the dimension n+1, independent of q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For unbounded domain, there are several results in homogeneous Sobolev spaces(see [18]). However, we could not obtain (3.3) in general.…”
Section: Technical Lemmas and Their Proofsmentioning
confidence: 99%
“…For unbounded domain, there are several results in homogeneous Sobolev spaces(see [18]). However, we could not obtain (3.3) in general.…”
Section: Technical Lemmas and Their Proofsmentioning
confidence: 99%
“…For unbounded domain, there are several results in homogeneous Sobolev spaces(see [25]). However, we could not obtain (2.22) in general.…”
Section: Notations and Resultsmentioning
confidence: 99%
“…However, there are several results in homogeneous Sobolev spaces (see [17]). Since R 2 \Ω is a bounded, open and simple connected domain with C ∞ Jordan boundary, in [10] it has been shown that there exists a smooth biholomorphism T : Ω → R 2 \D, extending smoothly up to the boundary, mapping Γ to ∂D.…”
Section: Technical Lemmas and Their Proofsmentioning
confidence: 99%